An efficient handwritten Bangla character recognition system using computer vision and natural language processing - Aishi, Tanusree Das; Iltimas, Md. Seam; Wakil, Mirza Azwad; Barua, Pritam (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.